2009
DOI: 10.1002/adsc.200800624
|View full text |Cite
|
Sign up to set email alerts
|

Iodine‐Catalyzed Suzuki–Miyaura Coupling Performed in Air

Abstract: Suzuki-type coupling reactions can be performed directly in air using a catalytic system composed of iodine, potassium carbonate, and polyethylene glycol 400 (I 2 /K 2 CO 3 /PEG-400). Iodine was found to be an effective additive for accelerating these couplings. The methodology is also suitable for the coupling of (E)-b-bromostyene with phenylboronic acid, with retention of the double bond geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…4-Methoxy-1,1'-biphenyl: [7] Table 1 and Table 2 -N,N-dimethyl-[1,1'-biphenyl]-4-amine: [13] 4'-Methoxy-[1,1'-biphenyl]-4-carbonitrile: [14] 2-(4-Methoxyphenyl)thiophene: [7] 3-(4-Methoxyphenyl)pyridine: [15] Table 2 N,N-Dimethyl-[1,1'-biphenyl]-4-amine: [13] Table 2 4-Fluoro-1,1'-biphenyl: [16] 4-Fluoro-4'-methyl-1,1'-biphenyl: [17] Table 2 4'-Fluoro-[1,1'-biphenyl]-4-carbonitrile: [17] Table 2 4-Chloro-4'-fluoro-1,1'-biphenyl: [16] Table 2, Entries 12 and 13. Purified by flash chromatography (pentane) to afford a white solid which contains a small amount of 4,4'-dichloro-1,1'-biphenyl.…”
Section: General Procedures For Aerobic Heterocoupling Of Two Grignardmentioning
confidence: 99%
See 1 more Smart Citation
“…4-Methoxy-1,1'-biphenyl: [7] Table 1 and Table 2 -N,N-dimethyl-[1,1'-biphenyl]-4-amine: [13] 4'-Methoxy-[1,1'-biphenyl]-4-carbonitrile: [14] 2-(4-Methoxyphenyl)thiophene: [7] 3-(4-Methoxyphenyl)pyridine: [15] Table 2 N,N-Dimethyl-[1,1'-biphenyl]-4-amine: [13] Table 2 4-Fluoro-1,1'-biphenyl: [16] 4-Fluoro-4'-methyl-1,1'-biphenyl: [17] Table 2 4'-Fluoro-[1,1'-biphenyl]-4-carbonitrile: [17] Table 2 4-Chloro-4'-fluoro-1,1'-biphenyl: [16] Table 2, Entries 12 and 13. Purified by flash chromatography (pentane) to afford a white solid which contains a small amount of 4,4'-dichloro-1,1'-biphenyl.…”
Section: General Procedures For Aerobic Heterocoupling Of Two Grignardmentioning
confidence: 99%
“…Purified by flash chromatography (pentane) to afford a white solid which contains a small amount of 4,4'-dichloro-1,1'-biphenyl. 4-Chloro-1,1'-biphenyl: [18] 4-Chloro-4'-methoxy-1,1'-biphenyl: [18] 2-(4-Fluorophenyl)thiophene: [15] Table 2 3-(4-Fluorophenyl)pyridine: [17] 2-(4-Fluorophenyl)furan: [19] Table 2 2-Methoxy-1,1'-biphenyl: [16] 3-Chloro-1,1'-biphenyl: [20] 3-Methoxy-1,1'-biphenyl: [16] Table 2 …”
Section: General Procedures For Aerobic Heterocoupling Of Two Grignardmentioning
confidence: 99%
“…In the present study, iodine was investigated as a catalyst for the reaction of alcohols with nitriles. Recently, iodine has been investigated as a potential efficient catalyst in several organic reactions because it has low toxicity [6][7][8][9][10][11][12][13][14][15][16][17][18] . In this study, we also investigated solvent-free conditions, from the viewpoint of green chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…(E) Mao et al 10 have found that the transition-metal-catalyzed Suzuki coupling could also be well performed in air using iodine as effective catalyst. In addition, the newly developed metal-free protocol was also applicable for the coupling of (E)-b-bromostyene with phenylboronic acid, with retention of the double bond geometry.…”
Section: Abstractsmentioning
confidence: 99%